Motor activity of high class female boxers in competitive fights - Akopyan, A. O.; Domuladzhanova, O. V. (Vestnik sportivnoj nauki; Sports science bulletin, 2019)
The article presents the results of studies of competitive activities of high-class female boxers in the main competitions of 2018 - European and World Championships. Correlation of forces in the European and world arena by countries and weight categories has been shown. The analysis of competitive fights is based on the density characteristic of competitive combat, which is calculated as the ratio of the number of strikes per unit of time (min). It is found that Asian female boxing have substantial preferences in comparison with European ones.